(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
The article gives examples of some terms and concepts related to types of tourism, including religious tourism, such as the origin of the term pilgrimage, religious, excursion, travel, religious research, language, history, content, definition and etymology